2015
DOI: 10.3109/07434618.2015.1047532
|View full text |Cite
|
Sign up to set email alerts
|

AAC Interventions for Individuals with Autism Spectrum Disorders: State of the Science and Future Research Directions

Abstract: Augmentative and alternative communication (AAC) provides a means of effective communication to individuals with autism spectrum disorder (ASD), many of whom are unable to use conventional speech effectively. The purposes of this article are (a) to summarize and synthesize the last few decades of research on the use of AAC with people with ASD; (b) to indicate implications of this research for stakeholders such as people with ASD, their family members, and educators with whom they work; and (c) to outline prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 108 publications
1
65
0
19
Order By: Relevance
“…It cannot be assumed that the use of AAC alone will lead to functional oral communication without a therapeutic plan. 368 Current scientific evidence does not support the use of facilitated communication in which a nonverbal individual is guided to communicate. 369,370 This differs from AAC, in which the individual is taught to communicate independently.…”
Section: The Picture Exchange Communicationmentioning
confidence: 99%
“…It cannot be assumed that the use of AAC alone will lead to functional oral communication without a therapeutic plan. 368 Current scientific evidence does not support the use of facilitated communication in which a nonverbal individual is guided to communicate. 369,370 This differs from AAC, in which the individual is taught to communicate independently.…”
Section: The Picture Exchange Communicationmentioning
confidence: 99%
“…Intervenciones basadas en terapias Dentro de este conjunto de estrategias encontramos las intervenciones basadas en la comunicación, las intervenciones basadas en la familia y las terapias combinadas: -Los sistemas alternativos y/o aumentativos de la comunicación, también conocidos como SAAC (Ganz, 2014), constituyen herramientas de interacción distintas al lenguaje oral cuya finalidad es aumentar y/o compensar los problemas de comunicación que presentan muchos niños con TEA. Uno de los principales métodos que se engloban dentro de esta categoría es conocido como Picture Exchange Communication System (PECS), un sistema de comunicación por intercambio de imágenes, en castellano (Bondy & Frost, 1994).…”
Section: Intervenciones Evolutivasunclassified
“…Given that approximately 25 to 30% of this population have impaired vocal communication repertoires (Klinger et al 2002;Wodka et al 2013), teaching the use of an augmentative and communicative system (AAC) such as manual sign language, picture exchange, or speech-generating devices (SGDs) may be beneficial to establish verbal behavior repertoires (Beukelman and Mirenda 2005;Ganz 2015). AAC systems can be categorized into two groups: unaided systems (e.g., gestures or manual sign) which do not require external equipment and as aided systems (e.g., SGDs, picture symbols, or written communication) which require the use of external equipment or a device (Beukelman and Mirenda 2005;Sigafoos et al 2007).…”
mentioning
confidence: 99%
“…The majority of studies investigating procedures for teaching individuals with ASD to use SGDs have focused on basic mands (Alzrayer et al 2014;Ganz 2015). In a review of AAC interventions by Ganz (2015), which focused on the state of the science, one area of future research directions identified was the need to conduct research on other types of communication skills, such as socially motivated communication skills.…”
mentioning
confidence: 99%
See 1 more Smart Citation